Hypoxia training for sea-level performance. Training high-living low - Hoppeler, H.; Vogt, M. (Advances in Experimental Medicine and Biology, 2001)
It is widely accepted that prolonged exposure to extreme altitude is detrimental for exercise performance and muscle structure. Moreover, highly trained subjects seem to suffer more under hypoxic conditions than untrained people. When using hypoxia as an ergogenic stimulus in athletes, it has thus become customary to limit hypoxia exposure in terms of altitude and duration of exposure in order to achieve defined physiologic goals. If hypoxia application is limited to the duration of training sessions, specific hypoxia responses on the molecular level in skeletal muscle tissue can be demonstrated. Hypoxia inducible factor 1 (HIF-1alpha mRNA) is upregulated after 6 weeks of endurance training in hypoxia (equivalent to an altitude of 3850 m) in previously untrained subjects. This upregulation is independent of training intensity but not observed in subjects training under similar conditions in normoxia. High intensity training in hypoxia further results in an increase of vascular endothelial growth factor (VEGF) mRNA, capillarity and myoglobin mRNA. These results suggest that hypoxia training results in improvements of the oxygen transfer capacity in skeletal muscle tissue. They thus offer a plausible explanation for the observation that effects of hypoxia training in athletes can best be demonstrated when performance tests are carried out in hypoxia. Beneficial effects of "training high-living low" for sea level performance of athletes can be inferred from the structural changes observed in muscle tissue; however, the functional improvements remain to be demonstrated directly.